The Study of Quality Living Environment for Temporary Construction Workers' Accommodation in Malaysia - Zubir, Hazwan Bin; Rahim, Asiah Abdul (International Journal of Environment, Architecture, and Societies, 2021)
This research is to study the quality of living environment in workers’ accommodation for construction workers in Malaysia. In Malaysia, workers’ accommodation known as rumah kongsi. The research aim to identify appropriate and quality of living environment for construction workers. Majority the construction workers accommodation in Malaysia are currently in a poor condition. The poor condition of accommodation for construction workers have raised many issues affecting their surroundings and built environment. Some of the issues include health, social and finance. However, there are initiatives made by the Malaysian government especially Construction Industry Development Board (CIDB) and Kuala Lumpur City Hall (KLCH) in which they have come out with guidelines in providing accommodation for the construction workers. Previous studies showed that some developers and contractors providing improper and inadequate living environment for the construction workers, which lead to several issues, including safety and poor living facilities. The objectives of the studies, firstly to study the existing code of practice and guidelines in providing workers accommodation, secondly, to evaluate the existing workers accommodation in Malaysia and finally to propose the good, safety and practical living environment for workers accommodation. The methodology apply in this study include mix method or combine method which are, interview, case study, observation and content analysis. The data obtained from various methods are using descriptive analysis. In conclusion, this research findings attempts to provide guidelines and model of the most suitable living environment for workers accommodation in construction industry in Malaysia.